“Very strong” turnpike effect in a non-stationary Gale economy with investments, multilane turnpike and limit technology - Emil Panek (Economics and Business Review, 2023)
This article presents a multiproduct model of a non-stationary Gale-type economy  with  technology convergent to a certain limit technology, in which changes in the production technology  (the dynamics of the Gale production spaces) are ruled by the size of investments. Thus, the considered model differs from the vast majority of the Gale-type models  considered in the mathematical economy.  With this assumption,  the so-called “very strong” version of the multilane production turnpike theorem in the Gale economy with investments is proved. According to the theorem, if  the optimal growth process in such an economy reaches the multilane turnpike, it remains on it from then on, except for, possibly the last period of the analysed economic horizon.